Effect of alcohol intoxication on the risk of venous thromboembolism: A nationwide retrospective cohort study. Issue 42 (October 2017) - Shen, Chih-Jung; Kao, Chia-Hung; Hsu, Tai-Yi; Chen, Chih-Yu; Lin, Cheng-Li; Shih, Hong-Mo
Abstract : Abstract: This study investigated whether alcohol intoxication (AI) increases the risk of venous thromboembolism (VTE) by using the Taiwan National Health Insurance Research Database (NHIRD). Using data from the NHIRD, we assembled 61, 229 patients with acute AI and randomly selected 244, 916 controls. Each patient was monitored from 2000 to 2011 to identify those who were subsequently diagnosed with deep vein thrombosis (DVT) and pulmonary embolism (PE). Cox proportional hazard regression analysis was conducted to determine the risk of VTE in the patients with AI compared with the controls. The incidence rate of DVT during the 10 years follow-up period was 9.36 per 10, 000 person-years and 2.07 per 10, 000 person-years in the AI and non-AI cohorts, respectively. Moreover, the incidence rate of PE was 4 per 10, 000 person-years in the AI cohort and 0.93 in the non-AI cohort. After adjustment for age, sex, and comorbidities, the risks of DVT and PE were 3.40 [95% confidence interval (CI) = 2.83–4.08] and 3.53 (95% CI = 2.69–4.65)-fold higher in the AI cohort than in the non-AI cohort. An increased incidence of VTE was observed among patients with AI. Therefore, physicians should carefully estimate the risk of VTE in patients with AI.